Artur Azevedo e o teatro - Santos, Kelly Cristina dos (2016)
Artur Azevedo, who is considered by critics as a man of the theater, wrote plays with features of the popular and bourgeois culture, with simple plot and everyday issues, he was strongly criticized for his musical comic production and, according to some critics, it is less valued. This research theme is the study of Azevedo‘s theater, specifically in the plays O Mambembe, O Dote and A Capital Federal. We had as a starting point some conceptions about the theater formulated by Schiller (1964), also a brief explanation for the period in which the author and his work are inserted, identifying the procedures and comic functions in the plays in a third phase. We had as a theoretical support, about comicality, to fundament the research, the study O Riso: Ensaio sobre a significação da comicidade, by the author Henri Bergson (2007). From the conducted study, we observe that the brazilian theater, in the analyzed period, reflected in its structure the necessity to talk about itself and its internal and external tensions. Through the study of the comic plays we could understand that they had a moralizing function, comicality was used to correct manners. We realize, therefore, that the active comic in that period has fulfilled the moralizing function of correcting human behaviors that are diverted from socially established standard, so for these diverted habits the comic bias has acted in order to reintegrate the individual to the social environment.